Adult drosophila melanogaster glutathione S-transferases: effects of acute treatment with methyl parathion - Alias, Z.; Clark, A.G. (Academic Press Inc Elsevier Science, 2010)
The effect of acute treatment of methyl parathion (MP) on the expression of BSP/GSH-agarose purified glutathione S-transferases (GSTs) in Drosophila melanogaster was investigated. Using 2-D gel analysis of the identified Epsilon-class, only DmGSTE6 (100%) and DmGSTE7 (72%) demonstrated significant increases in expression, suggesting the possibility that both may be involved in MP metabolism. A smaller percentage increase was also observed in DmGSTD1 (18%), a known DDT dehydrochlorinase, DmGSTE3 and DmGSTE9 and a putative Epsilon-class GST, CG16936, were shown not to be responsive to the challenge. Our finding demonstrates that not all member of the Epsilon-class GST, which are known for their role in insecticide resistance, are immediately responsive to this toxic challenge. (C) 2010 Elsevier Inc. All rights reserved.